The Effect of Addition of Nano hydroxyapatite Powder of Anadara granosa Shells on Surface Roughness of Heat-cured Acrylic Resin - Aris Aji Kurniawan; Dian Noviyanti Agus Imam; Helmi Hirawan (Denta Journal Kedokteran Gigi, 2020)
Background: Heat-cured acrylic resin is one of the most widely used denture base materials. However, the residual monomer can reduce its mechanical properties, which affect physical properties such as surface roughness, resulting in high porosity—the results in the growth of fungal colonies. One way to improve these properties is to add a reinforcement material such as nano-hydroxyapatite (HAp) from the Anadara granosa shell. Nano-hydroxyapatite has a large surface area to act as a filler because of its strong bonding capacity and a smoother surface, and a higher density to improve mechanical properties. Purpose: This study aims to determine HAp powder's effect from the Anadara granosa shells on the surface roughness of heat-cured acrylic resin. Methods: This type of research used an experimental laboratory, research design posttest-only control group design. Twenty-four samples were used and divided into three groups: the acrylic resin group with 1%, 3% blood cockles shell HAp, and acrylic resin without HAp with simple random sampling. Results: The results showed that the lowest mean value of surface roughness was in a group with the addition of 3% HAp, at 1.696 ± 0.25058 µm. One-Way ANOVA test on roughness showed a significant difference between groups with p = 0.000 (p <0.05). Conclusion: This study concludes that there is an effect of HAp on the roughness of heat-cured acrylic resin.